Analysis of Factors Affecting Social Media Utilization of Extension Agents (Indian Journal of Extension Education, 2022)
Digitalization of communication networks through social media platforms is the most important tool to increase the reach and impact of agricultural advisory services. A profound need to study the extent of usage of social media by extension agents and factors influencing its usage was felt and to analyze the extent of usage, a composite index was developed during 2021 by using seven sub-indices that had a Cronbach alpha value of 0.903. To study the extent of usage 160 extension agents through a proportionate random sampling method were selected from Andhra Pradesh where the majority of the extension agents had a medium extent of usage which accounts for 44.37 per cent. Based on the correlational analysis it is found that innovative proneness (p<0.05), scientific orientation, job perception, technology management orientation, information management orientation, orientation towards extension service profession have a significant and positive correlation with the extent of usage of social media at 0.01 level of significance. Based on stepwise regression analysis it revealed that five variables were a good fit with an R-square of 35.7 per cent. The findings may help in framing a social media-led extension strategy by extension organizations and government bodies to reach the grassroots of the rural communities.